2015
DOI: 10.1016/j.engstruct.2015.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of cold-formed steel portal frames for stressed-skin action using genetic algorithm

Abstract: , R. M. (2015). Optimal design of cold-formed steel portal frames for stressed-skin action using genetic algorithm. Engineering Structures, 93, 36-49. DOI: 10.1016/j.engstruct.2015 Optimal design of cold-formed steel portal frames for stressed-skin action using genetic algorithm This paper describes a stressed-skin diaphragm approach to the optimal design of the internal frame of a cold-formed steel portal framing system, in conjunction with the effect of semi-rigid joints. Both ultimate and serviceability li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…A design optimization described by Phan et al [4,5] demonstrated that topology can have a significant effect on minimizing the cost of the primary members per meter square of the building. Furthermore, unlike conventional hot-rolled steel portal frames, where the purlin spacing is typically around 1.8 m, with cold-formed steel portal frames there is often a need to have a smaller spacing in order to provide more restraint to the column and rafter members.…”
Section: Notationmentioning
confidence: 99%
“…A design optimization described by Phan et al [4,5] demonstrated that topology can have a significant effect on minimizing the cost of the primary members per meter square of the building. Furthermore, unlike conventional hot-rolled steel portal frames, where the purlin spacing is typically around 1.8 m, with cold-formed steel portal frames there is often a need to have a smaller spacing in order to provide more restraint to the column and rafter members.…”
Section: Notationmentioning
confidence: 99%
“…However, design on a bare frame was carried out, neglecting the serviceability limit state. More recently, Phan et al (2015) and Wrzesien et al (2016) considered the effect of stressed-skin on cladded portal frame buildings. Through focusing only on optimising the material cost of main frame, those researchers have not considered the effect of the material cost of the secondary members (i.e., purlins, side rails and cladding) on the overall cost of the building.…”
Section: Introductionmentioning
confidence: 99%
“…The CFS framing system is designed to both ultimate and serviceability limit states using the The Steel Construction Institute recommendations for deflection limits for portal frames (see Table 1). It should be noted that the length of building is long enough to neglect the stressedskin effect through cladding system (Phan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Technologies 2017, 5, 81 3 of 13 stressed-skin on cladded portal frame buildings is recently considered [15][16][17][18], in which the influence of knee brace joint at eaves was investigated as a fixed configuration. Since GAs are unconstrained optimization techniques, constraint handling approaches therefore play an important role in its implementation.…”
Section: General Description Of Long-span Cold-formed Steel Portal Frmentioning
confidence: 99%
“…Also, influence of pitch of the roof and the frame spacing was investigated in term of topology variables. The effect of stressed-skin on cladded portal frame buildings is recently considered [15][16][17][18], in which the influence of knee brace joint at eaves was investigated as a fixed configuration.…”
Section: Introductionmentioning
confidence: 99%